Phenotypic stress response does not influence the upper thermal tolerance of male Atlantic salmon (Salmo salar) - Ignatz, Eric H.; Zanuzzo, Fabio S. [UNESP]; Sandrelli, Rebeccah M.; Clow, Kathy A.; Rise, Matthew L.; Gamperl, A. Kurt (Elsevier B.V., 2021)
Fish can be identified as either low responders (LR) or high responders (HR) based on post-stress cortisol levels and whether they exhibit a proactive or reactive stress coping style, respectively. In this study, male Atlantic salmon (Salmo salar) from 17 families reared at 9 degrees C were repeatedly exposed to an acute handling stress over a period of four months, with plasma cortisol levels measured at 1 h post-stress. Fish were identified as either LR or HR if the total Z-score calculated from their cortisol responses fell into the lower or upper quartile ranges, respectively; with intermediate responders (IR) classified as the remainder. Salmon characterized as LR, IR or HR were then subjected to an incremental thermal challenge, where temperature was raised at 0.2 degrees C day(-1) from their acclimation temperature (12 degrees C) to mimic natural sea-cage farming conditions during the summer in Newfoundland. Interestingly, feed intake remained high up to 22 degrees C, while previous studies have shown a decrease in salmon appetite after similar to 16-18 degrees C. After the first three mortalities were recorded at elevated temperature, a subset of LR and HR salmon were exposed to another acute handling stress event at 23.6 degrees C. Basal and post-stress measurements of plasma cortisol, glucose and lactate did not differ between stress response phenotypes at this temperature. In the end, the average incremental thermal maximum (ITMax) of LR and HR fish was not different (25.1 degrees C). In comparison, the critical thermal maximum (CTMax; temperature increased at 2 degrees C h(-1)) of the remaining IR fish that had been held at 12 degrees C was 28.5 degrees C. Collectively, these results: 1) show that this population of Atlantic salmon is very thermally tolerant, and further question the relevance of CTMax in assessing responses to real-world temperature changes; and 2) indicate that characterization of stress phenotype at 9 degrees C is not predictive of their stress response or survival at high temperatures. Therefore, selection of fish based on phenotypic stress response at low temperatures may not be beneficial to incorporate into Atlantic salmon breeding programs, especially if the goal is to improve growth performance and survival at high temperatures in sea-cages.
Keywords: Atlantic salmon; Stress; Cortisol; Thermal tolerance; Climate change